IMPLEMENTASI PROGRAM GIZI UNTUK PENURUNAN STUNTING: Studi Kasus Pemerintah Daerah Kabupaten Lombok Utara - Laksmiwati, Luh Gede; Ikhsan, Muhammad Ali; Warlina, Lina (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
Stunting has become a national problem, even in every year there are 27.67% of malnutrition problems in Indonesian children. This problem demands the seriousness of the central, regional and related parties. This research is intended to see the impact of the nutrition program on reducing stunting problems. The determination of research subjects was carried out by non-probability with a purposive sampling technique. The main informants in this study were: Puskesmas nutrition service implementers and triangulation informants, namely: the Head of the Health Service, the Head of the General and Civil Service Sub-Section, the Head of the Nutrition Section, the Head of the Tanjung Puskesmas, the Village Head, the posyandu cadres, and the posyandu targets. Data collection was carried out by in-depth interviews, observation and documentation study. The research location was conducted in Medana Village, North Lombok Regency. The results showed that the implementation of the nutrition program in North Lombok Regency has not run optimally due to the lack of socialization in the form of communication between relevant officials, inadequate availability of resources (human and budget), inconsistent attitudes of implementers towards SOPs which are still lacking due to weak supervision, and bureaucratic channels. too long and the implementation relationship pattern is limited. From various aspects of the implementation of nutrition program policies to reduce stunting, when analyzed based on the theory of George Edwards III, the position of North Lombok Regency in the process of implementing a nutrition program to reduce stunting has not been optimally successful.